MIKROENKAPSULASI Lactobacillus sp. DENGAN TEKNIK EMULSI DAN APLIKASINYA PADA DODOL SIRSAK - Anis Usfah Prastu Jati; Betty Sri Laksmi Jenie; Suliantari - (Jurnal Teknologi dan Industri Pangan, 2015)
Two probiotic strains Lactobacillus acidophilus 2B4 and L. rhamnosus R23 were microencapsulated by an emulsion technique using sodium alginate and vegetable oil. The present study aimed to enhance probiotic survival on their application in the production of soursop sweet cakes (dodol sirsak) and their stability during storage at room temperature. The probiotic biomasses were mixed with 3% sodium alginate and then added dropwise into a mixture of soybean oil and Tween 80. The microencapsulation technique applied resulted in excellent survival (95-96%) for both Lactobacillus sp. strains. Encapsulation significantly improved the survival of probiotics (P<0.05) during exposure to heat process (60, 65, and 70°C for 20 min), low pH (pH 2) and bile salt (0.5%). However, encapsulation did not alter the ability of both probiotics in inhibiting the growth of Escherichia coli ATCC 25922. The viability of encapsulated strains in soursop sweet cakes were improved to the adequate amount, i.e. 6 log CFU g-1 up to 3 and 2 weeks storage, compared to that of controls which lasted to 4.3 and 2.5 log CFU g-1, for L. acidophilus 2B4 and L. rhamnosus R23, respectively, in a week of storage.